Transcripts from the Epstein-Barr virus BamHI A fragment are detectable in all three forms of virus latency. - Brooks, L A (1993)
An unexpected feature of the latency II form of Epstein-Barr virus (EBV) infection seen in the epithelial tumor nasopharyngeal carcinoma (NPC) is the presence of spliced polyadenylated RNAs encoded from the BamHI A fragment of the viral genome and running in the opposite orientation to several BamHI-A lytic cycle genes. The importance of these BamHI-A transcripts and the specificity of their association with NPC remain to be determined. In this study, we examined the extent to which such RNAs are present in other transcriptionally distinct forms of EBV latency seen in B cells. Two independent assays of BamHI-A transcription were employed: amplification across defined splice junctions in cDNAs, using the polymerase chain reaction, and in situ hybridization with a radiolabeled riboprobe specific for a putative open reading frame downstream of these splice junctions. Such methods, which easily detected BamHI-A RNAs in fresh NPC biopsies and transplantable NPC lines, also revealed consistent expression of these transcripts in all EBV-positive Burkitt's lymphoma cell lines displaying the highly restricted latency I form of infection (BamHI-F promoter usage) as well as in all EBV-transformed lymphoblastoid cell lines (LCLs) displaying the latency III form of infection (BamHI-C/W promoter usage). Expression in established LCLs, occurring irrespective of virus producer status, was not a consequence of continued in vitro passage; thus, appropriately spliced BamHI-A transcripts could be amplified from normal B cells within 1 day of their experimental infection in vitro, along with BamHI-C/W promoter-initiated but not BamHI-F promoter-initiated mRNAs. In situ hybridization both on Burkitt's lymphoma cell lines and on LCLs showed that essentially every cell contained BamHI-A transcripts, although at levels apparently lower than those observed in NPC. We conclude that expression of the BamHI-A RNAs is a consistent feature shared by all known forms of latent EBV infection.